Sistema de classificação de nível de competência profissional para profissionais em contexto de projetos com utilização de inteligência artificial - Luiz Neto, Alcides (2023)
What determines a person's ability to carry out a professional activity goes beyond knowledge of techniques and execution tools related to that activity. Professional development also depends on behaviors and attitudes that increase the ability to understand the scenario in which it is inserted so that it is possible to adapt to needs. Despite the relevance of dealing with competences at the individual level, or in a grouped way, it is also necessary to understand what qualifies the competence of a professional. Thus, the development of professionals depends on the acquisition of knowledge, the development of skills and an adequate attitude to perform a professional activity. In this context, the general objective of this thesis was to propose a system to classify the level of professional competence of professionals from different specialties in the context of projects. That said, the research departed from the assumptions presented in the model by Dreyfus and Dreyfus (1980). The research was structured by three connected studies following sequential logic combining qualitative and quantitative data. Study 1 reviewed Dreyfus and Dreyfus' (1980) skill acquisition theory to generate a conceptual model for classifying professional competence. Study 2 sought to understand how patent products perform the assessment of competencies in organizations. Finally, study 3 developed and validated a system for classifying the level of professional competence of professionals from different specialties in the context of projects. As a result of this research, based on the validation of the system to help organizations and professionals in assessing the level of professional competence, using the Fibonacci sequence as a basis, providing an attitude adjustment mechanism and diagnosis that can guide professionals and organizations in appropriate actions and investments to enhance individual and collective professional development, using, in addition to a solid conceptual structure, generative artificial intelligence as a personalization enhancer. Thus, individualized, and personalized response reports were generated with evolution recommendation and action plans relying on the use of generative AI. As a theoretical contribution, the research advances in discussions on the development of professional competence in the context of projects, constituting a matrix of competences based on 10 dimensions and eight levels, consolidating theory and organizing knowledge. The use of Fibonacci also contributes to the aspect of understanding the levels of professional competence, which does not occur in a conventional arithmetic progression. As a practical contribution, the instrument will help companies and actors in the context of projects to identify potential talent, improving retention and correctly directing investments in development, in feedback processes and in the construction of individual development plans, becoming a tool for self-knowledge . This research is aligned with research line 2: "Project Management", linked to the Graduate Program in Project Management - PPGP UNINOVE, as well as this thesis is also aligned with other researches linked to the axis-projects "Project Management". People and Project Management”.